2006
DOI: 10.1038/sj.npp.1301222
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Gating and Dopamine Function in Postpartum Rats

Abstract: There is much speculation regarding the effects of estrogen withdrawal at the end of pregnancy on forebrain dopamine, however, few studies have directly examine changes in this system postpartum. The present work sought to determine what changes in forebrain dopamine function occur in the postpartum rat. Specifically, prepulse inhibition of the acoustic startle response (PPI) was measured in primiparous female rats on postpartum day 2 (PPD2) or 14 (PPD14) following treatment with saline or the dopamine D2 agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…Two studies reported that termination of pseudopregnancy, induced by injections with pregnant mare serum gonadotropin and human chorionic gonadotropin, caused anxiety-like behavior in the elevated plus which could be resolved by progesterone injections (Bitran and Smith, 2005;Bitran and Solano, 2005). In contrast to the above mentioned studies open field behavior in lactating rats did not differ from diestrous females at 2 days and 14 days postpartum (Byrnes et al, 2007). As the rats were lactating, the hormonal changes accompanying lactation might have opposed the anxiogenic effects of progesterone withdrawal, since anxiolytic effects of the lactation hormone oxytocin have been reported (Uvnas-Moberg, 1998).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Two studies reported that termination of pseudopregnancy, induced by injections with pregnant mare serum gonadotropin and human chorionic gonadotropin, caused anxiety-like behavior in the elevated plus which could be resolved by progesterone injections (Bitran and Smith, 2005;Bitran and Solano, 2005). In contrast to the above mentioned studies open field behavior in lactating rats did not differ from diestrous females at 2 days and 14 days postpartum (Byrnes et al, 2007). As the rats were lactating, the hormonal changes accompanying lactation might have opposed the anxiogenic effects of progesterone withdrawal, since anxiolytic effects of the lactation hormone oxytocin have been reported (Uvnas-Moberg, 1998).…”
Section: Discussionmentioning
confidence: 71%
“…In lactating rats a decrease in PPI has been reported. Furthermore, the startle amplitude was increased at the 14th but not on the 2nd day postpartum (Byrnes et al, 2007). In humans the startle response magnitude and PPI do not change during the first 3 postpartum days when compared to pregnancy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, if one looks at the individual disorders, some possible connections are found. For example, in schizophrenia a dysregulation of sensory motor gating occurs (Braff and Geyer, 1990) and in mothers, changes in sensory motor gating also transpire (Byrnes et al, 2007). Thus, the same genes promoting alterations in sensory motor gating may be involved in both mothers and individuals with schizophrenia.…”
Section: Association With Other Mental Health Disorder Genes That mentioning
confidence: 99%
“…In addition to negative mood symptoms, objective manifestations of physiological arousal, such as the acoustic startle response, are also influenced by estradiol and progesterone (Byrnes et al, 2007;Toufexis et al, 1999;Vaillancourt et al, 2002;Van den Buuse and Eikelis, 2001). The acoustic startle response is increased in an animal model of PMDD , and was recently also shown to be increased in the luteal phase of PMDD patients (Epperson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%